Navigating agroecological urbanism: examining linkages and interdependencies within alternative food networks - Zerbian, Tanya; López-García, Daniel (Frontiers in Sustainable Food Systems, 2024)
In pursuing agroecological urbanism – a strategic endeavor to dismantle disempowering structures within urban food systems through cultivating mutual interdependencies – alternative food networks (AFNs) emerge as pivotal catalysts for transformative change. Indeed, there are increasing arguments for AFNs working on diverse issues to pool resources and address food system challenges from multiple perspectives under a common frame. However, a pressing need exists for greater clarity on tensions and challenges in establishing a network of AFNs within a shared framework, such as that fostered by agroecological urbanism. This study explores impediments to organizing AFNs into transformative networks, drawing insights from two diverse urban contexts – Preston, England, and Vitoria-Gasteiz, Basque Country – using a case study methodology comprising online semi-structured interviews and participant observation. Our findings underscore three primary barriers to this process: divergent conceptualizations of food questions, education and awareness-raising as a limited convergence point, and constrained resources. Such barriers generate a practical divorce between social and environmental goals in the experiences analyzed. Central to this division is also the pivotal question of the subject of justice – whether AFNs advocate primarily for urban citizens’ interests or prioritize peri-urban and rural farmers’ concerns. The analysis highlights the need to develop inclusive socio-ecological narratives within the overarching framework of agroecological urbanism as a critical step in fostering collaborative coalitions among AFNs that move beyond individualized change. Building these coalitions would depend on funding availability for long-term strategic collaborative efforts, emphasizing the crucial role of public authorities in such processes.